Molluscum Contagiosum: Review and Update on Management. Issue 5 (September 2017) - Forbat, Emily; Al‐Niaimi, Firas; Ali, Faisal R.
Abstract: Molluscum contagiosum (MC) is an infectious dermatosis that commonly presents in children and immunocompromised individuals. Although lesions usually resolve spontaneously after several months, they can be symptomatic and cause psychosocial distress. We review the evidence underlying treatment methods available for MC lesions, including potassium hydroxide, salicylic acid, hydrogen peroxide, retinoids, cantharidin, cryotherapy, curettage, and pulsed dye laser to aid practicing dermatologists in therapy selection.